Population structure and the impact of regional and local habitat isolation upon levels of genetic diversity of the endangered damselfly Coenagrion mercuriale (Odonata: Zygoptera) - Watts, P.C.; Saccheri, I.J.; Kemp, Stephen J.; Thompson, D.J. (Wiley, 2006)
1. Coenagrion mercuriale is one of Europe's most threatened damselflies. There is concern for the long-term persistence of many of its U.K. colonies because adult lifetime movement is limited, making isolated populations susceptible to extinction. 2. Using 14 microsatellite loci we characterised levels of genetic diversity, evidence for a recent decline and the spatial genetic structure for C. mercuriale population in Wales, U.K. 3. Spatial isolation is not an absolute predictor of low genetic diversity at either local or regional scales. 4. One population inhabiting a remote, edge of range site is genetically impoverished with levels of variability (at microsatellite loci) among the lowest reported for any insect species. 5. Agricultural land and high ground are physical barriers to dispersal by adults. 6. Consistent with work from elsewhere, movement by mature C. mercuriale in Pembrokeshire is sufficient to prevent significant genetic differentiation throughout a habitat matrix of some 3–4 km if the suitable habitat sites are <2 km apart and lack barriers to movement. Even within a good habitat matrix, however, genetic isolation by distance develops within 10 km.